Holy legionary youth: fascist activism in interwar Romania - Clark, Roland (Cornell Univ. Press, 2015)
The roots of ultra-nationalism -- Youthful justice -- Mobilizing support -- Elections, violence, and discipline -- The power of print -- Iron-clad breasts and lily-white souls -- Salvation and sacrifice -- Rise and fall